2021
DOI: 10.1177/08854122211018379
|View full text |Cite
|
Sign up to set email alerts
|

Defining Public Interest in Planning: A Review

Abstract: Public interest as the main content and purpose of planning is a fuzzy concept in planning literature. The body of literature on the public interest is so complex and diverse that makes it difficult to define and use the concept. In this study, the various definitions are categorized to achieve a framework of the definition of public interest. In addition to being more comprehensive than previous studies, this categorization identifies the main dimensions of a comprehensive definition of public interest. It pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…Commitment to the public interest is so complex and diverse that it is difficult to define and use the concept (Dadashpoor and Sheydayi 2021). It is geared towards doing good in the public interest.…”
Section: Commitment To the Public Interestmentioning
confidence: 99%
“…Commitment to the public interest is so complex and diverse that it is difficult to define and use the concept (Dadashpoor and Sheydayi 2021). It is geared towards doing good in the public interest.…”
Section: Commitment To the Public Interestmentioning
confidence: 99%
“…A study by Primc and Slabe-Erker [105] showed that the most important challenge in making decisions on health risk prevention is to maintain a balance between the reduction of the risk of a SARS-CoV-2 transmission and economic costs, taking into account the principles of sustainable development. The issue of striking a balance between health objectives and economic costs thus remains a key challenge, embedded in the discussion of balancing rationales, in shaping public interest [106]. The variability and diversity of a health situation (and its risks) caused by a pandemic lead to the conclusion that this balancing must be continuous, dynamic and based on flexible criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In the above context, the findings of the available studies suggested that an urban health-oriented research approach should be adopted in which urban strategies and project activities aim to continuously improve people's health. This was particularly emphasized by Fior and Mpampatsikos [111] and Bandarin et al [106], who called for more research on cultural, legal and political differences in pandemic control effectiveness. It would be interesting in the future to relate these studies to the levels of social and health inequalities that were observed.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Primc and Slabe-Erker [92] showed that the most important challenge in making decisions on health risk prevention is to maintain a balance between the reduction of risk of SARS-CoV-2 transmission and economic costs, taking into account the principles of sustainable development. The issue of striking a balance between health objectives and economic costs thus remains a key challenge, embedded in the discussion of balancing rationales in shaping the public interest [93]. The variability and diversity of the health situation (and its risks) caused by a pandemic lead to the conclusion that this balancing must be continuous, dynamic, and based on exible criteria.…”
Section: Discussionmentioning
confidence: 99%